Polymorphism of Growth Factor 1 gene in New Zealand rabbit breed in Cu Chi farm, Vietnam - Bui, Phu Nam Anh; Nguyen, Van Hop; Le, Ba Chung; Ngo, Minh Tri (Vietnam Journal of Biotechnology, 2025)
Rabbit husbandry in Vietnam is a growing sector of the livestock industry, offering significant potential for sustainable meat production and economic development, particularly in rural areas. Rabbits are well-suited to Vietnam's tropical climate due to their adaptability, high reproductive rates, and relatively low resource requirements compared to larger livestock. The New Zealand White breed and various local crossbreeds are the most commonly raised rabbits, valued for their resilience, efficient feed conversion, and quality meat. The Growth Hormone 1 (GH1) gene encodes the growth hormone (GH), a pivotal endocrine regulator essential for normal development and metabolic function across animal species. GH is synthesized in the anterior pituitary gland and plays a central role in growth, tissue repair, and metabolism. This study investigates the polymorphism of the Growth Hormone 1 (GH1) gene and its association with growth performance in New Zealand white rabbits reared at Cu Chi Farm, Vietnam. Fifty-six rabbits were genotyped for the GH1 c.-78C>T polymorphism using the PCR-RFLP method, and their body weight at 70 days of age was measured. The genotypic frequencies were distributed as CC (28.57%), CT (44.64%), and TT (26.79%), with allele frequencies of 0.515 for C and 0.485 for T. Statistical analysis revealed that heterozygous CT rabbits exhibited significantly higher body weight (1885 ± 17.04 g) compared to CC (1785.45 ± 12.05 g) and TT (1752 ± 19.35 g) genotypes. The equal allele frequency observed may result from the selective advantage of the heterozygous genotype, maintaining a balanced genetic structure within the population. These findings suggest that GH1 polymorphism influences growth traits and highlight its potential as a genetic marker for selective breeding programs aimed at improving growth efficiency in rabbits. Further studies are recommended to explore additional genetic markers and validate these results on a larger scale.